New families, old scripts : a guide to the language of trauma and attachment in adoptive families - Archer, Caroline, 1948- (Jessica Kinglsey Publishers, 2006)
Most adopted children and their families will, sooner or later, encounter the challenges of dealing with unresolved attachment issues or early traumatic experiences. New Families, Old Scripts is an accessible introduction to understanding these challenges and helping children and their families to develop a shared language and understanding of one another. Steeped in the experience of the authors, the book offers a wealth of practical guidance and intervention in a no-nonsense style that will be readily understandable to both families and the professionals who work with them. Case examples bri.